2018
DOI: 10.1007/s00792-018-1009-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable marine microbial proteases for industrial applications: scopes and risks

Abstract: Thermostable proteases are important in biotechnological and industrial sectors, due to their stability against denaturing agents and chemicals. The feature that gives them such unique applicability is their reaction at high temperatures, which affords a high concentration of substrate, and less risk of microbial contamination. Nearly 65% of industrial proteases are isolated from marine microbial source, and they can significantly resist a wide range of organic solvents at high temperatures. The most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 132 publications
1
25
0
Order By: Relevance
“…Proteases are enzymes with many uses in biotechnology, from hydrolysis of proteins to reduction of allergenicity or production of bioactive peptides, to fine chemistry (production of dipeptides, resolution of racemic mixtures, etc.) being the detergent industry the main consumer of proteases [1,2,3,4,5,6,7,8]. Alcalase, a protease solution supplied by Novozyme, has subtilisin Carlsberg as main component and it is produced by a strain of Bacillus licheniformis .…”
Section: Introductionmentioning
confidence: 99%
“…Proteases are enzymes with many uses in biotechnology, from hydrolysis of proteins to reduction of allergenicity or production of bioactive peptides, to fine chemistry (production of dipeptides, resolution of racemic mixtures, etc.) being the detergent industry the main consumer of proteases [1,2,3,4,5,6,7,8]. Alcalase, a protease solution supplied by Novozyme, has subtilisin Carlsberg as main component and it is produced by a strain of Bacillus licheniformis .…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature for the maximum enzyme activity was found to be 45 °C, which implies that the enzyme is also thermostable (Briki et al 2016). Such thermostable proteases are important in biotechnological, and industrial applications due to their stability against denaturing agents, and other chemicals (Barzkar et al 2018). The enzyme shows maximum activity at pH 9, and hence can be classi ed as an alkaline protease.…”
Section: Application Of Protease In Contact Lens Cleansingmentioning
confidence: 98%
“…A large number of enzymes from deep-sea thermophilic microorganisms have been characterised to date (Table 1) [35], and thermophilic proteases, lipases and polymer-degrading enzymes, in particular, have found their way into industrial applications [11]. The diversity of deep-sea thermophiles makes them valuable in the search for novel thermostable proteolytic enzymes [56,57], which are attractive for use in the detergent, food and feed industries. Jin et al [44] reported the purification and characterisation of a thermostable and alkali-stable keratinase Ker02562 from Bacillus sp.…”
Section: Deep-sea Thermophilic Enzymesmentioning
confidence: 99%